The effect of underhand passing training methods on the accuracy of underhand passing among volleyball players - Mohammad Imam Fauzhi; Taufiq Hidayat; Mohammad Imam Fauzhi; Taufiq Hidayat (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
Accuracy underhand passing is an important basic technique in volleyball used to receive the ball from the opponent. Good accurascy underhand passing skills are crucial for a team's success in defending and building attacks. This study aims to determine the effect of variations in accurascy underhand passing exercises on accurascy underhand passing skills in female volleyball players at SMPN 18 Gresik. The research method used a quantitative approach with an experimental method, namely True Experimental Design with a Randomized Pretest–Posttest Control Group Design. The population in this study were all 15 female volleyball players at SMPN 18 Gresik, who were also used as samples. The research instrument was an accurascy underhand passing skill test. Data analysis was carried out using normality tests, homogeneity tests, and differences in pretest and posttest results. The results showed that the accurascy underhand passing skill data were normally distributed with a p (Sig) value > 0.05 and the data were homogeneous with a sig. p value > 0.05. The group given the training variations showed a significant increase compared to the control group. Based on these results, it can be concluded that variations in underhand passing exercises have an effect on accurascy underhand passing skills in female volleyball players at SMPN 18 Gresik. It is recommended that coaches and sports teachers implement variations of underhand passing exercises in a programmed manner to improve students' basic volleyball technical skills.